Re-Structuring Evaluation Findings into Useful Knowledge - Danielle Houston; Bernadette Wright; Steven E. Wallis (Journal of MultiDisciplinary Evaluation)
Background: A long research stream has shown that when knowledge is more structured it is more likely to be effective in practical application. Building on that research, the authors applied Integrative Proposition Analysis to visualize, integrate, and assess the quality and usefulness of knowledge gained from the NMAC (formerly National Minority AIDS Council) Strong Communities evaluation.